2014
DOI: 10.1007/s12160-014-9600-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Associations of Antecedent- and Response-Focused Emotion Regulation Strategies with Midlife Cardiovascular Disease Risk

Abstract: Background It is not known whether various forms of emotion regulation are differentially related to cardiovascular disease risk. Purpose The purpose of this study is to assess whether antecedent and response-focused emotion regulation would have divergent associations with likelihood of developing cardiovascular disease. Methods Two emotion regulation strategies were examined: reappraisal (antecedent-focused) and suppression (response-focused). Cardiovascular disease risk was assessed with a validated Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 41 publications
2
51
0
2
Order By: Relevance
“…Specifically, lesbians who usually concealed their identity had poorer self‐rated health and were more likely to be a current smoker than those who did not usually conceal their identity. Studies of the general population have found that chronic stress can be a stronger determinant of health among women 58,59 and there is some preliminary evidence indicating that maladaptive self‐regulatory processes may have more severe consequences for women's health 60 . These gender‐specific vulnerabilities may be an explanation behind our findings.…”
Section: Discussionmentioning
confidence: 49%
“…Specifically, lesbians who usually concealed their identity had poorer self‐rated health and were more likely to be a current smoker than those who did not usually conceal their identity. Studies of the general population have found that chronic stress can be a stronger determinant of health among women 58,59 and there is some preliminary evidence indicating that maladaptive self‐regulatory processes may have more severe consequences for women's health 60 . These gender‐specific vulnerabilities may be an explanation behind our findings.…”
Section: Discussionmentioning
confidence: 49%
“…Regulation of emotions through taking the perspective of others and cognitive reappraisal (attaching a different meaning to an experience), used extensively in mindfulness‐based stress‐reduction programmes and cognitive therapies, has been associated with decreased negative and increased positive emotions, and lower levels of C‐reactive protein and cardiovascular risk . Suppression of emotions has the opposite results …”
Section: Research On Modulators Of Empathy and Compassionmentioning
confidence: 99%
“…Regarding the latter process, the mPFC and ACC are critically implicated in the regulation of negative emotion, in particular cognitive reappraisal [45]. Cognitive reappraisal is a major clinical focus of behavioral interventions for depression and other affective disorders [46], and individual differences in the tendency to use cognitive regulation of emotion associates with preclinical markers of CVD [47]; hence, the role of these cortical structures in emotion regulation and CVD risk is an emerging line of research. Separately, the mPFC and ACC issue ‘brain-to-body’ visceromotor commands in the form of autonomic and cardiovascular responses to environmental stimuli [4850].…”
Section: Introductionmentioning
confidence: 99%